Noise Immunity Radio Link Model in Dynamic Intentional Exposure - S. V. Dvornikov; A. V. Pshenichnikov (Известия высших учебных заведений России: Радиоэлектроника)
To ensure the required interference immunity of a radio link is a crucial task nowadays. The existing solutions in this field are based on signal spectrum spreading methods. In the age of radio engineering development application of specific technical solutions when building a noise immune radio system is ineffective. In this case, one of the most challenging tasks is taking into account the dynamic effects on the radio link resources. The solution to this problem can be obtained by the development of complex operation algorithms for radio system. This paper proposes noise immune radio link model taking into account the dynamic intentional impact on its resources. A distinctive feature of the proposed approach is determination of radio link resource control strategy. For that purpose, a concept of vector of elementary control methods is introduced. On the base of the random process theory a noise immunity radio link model is developed.